Source credibility: A study of eWOM on social media and Chinese students’ travel choices - Chen, Lan (2013)
Background problem: Previous studies have found that source credibility of eWOM has impact on perceived persuasiveness of the source. Source credibility plays an important role in the effectiveness of eWOM. The more credibility a product is perceived, the more persuasiveness the information has. There are two models that are commonly used in studying the perceived credibility of the source of information, which are source credibility model (Perceived source credibility depends on expertise and trustworthiness.) and source attractiveness model (Perceived source credibility depends on familiarity, similarity and likeability). Purpose: Combining the two commonly used models, this study investigated the perceived credibility of sources on social media and its impact on Chinese students’ travel destination decisions. Method: In this study, a qualitative semi-structured interview approach was adopted. Chinese students were invited to recall and talk about their experience of using social media to gather travel information. After the answers were transcribed, they were coded into categories based on the meaning of the context. Findings: The results showed that higher perceived trustworthiness, expertise and attractiveness lead to higher perceived source credibility. Higher source credibility results in more persuasion. Keywords: Social media, source credibility, source attractiveness, response